Preparing educators to communicate and connect with families and communities - Schmidt, Patricia Ruggiano, 1944-; Edwards, Patricia A. (Language, literacy, and learning., 2005)
This unique and visionary text is a compilation of fascinating case studies by New York State teachers, parents and professors. These down-to-earth case studies highlight effective specific approaches to provide bridges between home and school and a look to the future for preparing teachers to communicate and connect with families and communities. This book promises to make a signifi-cant contribution to preparing teachers to engage all families and communities in the education of our children. It is filled with activities coming out of an incredible body of educational research done by the contributors. This book has given us the answers to the questions that Schmidt raised and it will move family involve-ment from high rhetoric to high practice. This book will change the way we prepare teachers and it is a must read for those in teacher education programs.